Is Interarterial Course a Requisite for Ischemia in Anomalous Origin of Coronary Arteries?. (July 2017) - Madan, Nitin; Lorber, Richard; Nento, Daniel; Mumtaz, Muhammad; Singh, Harinder R.
Anomalous origin of the left main coronary artery from the noncoronary sinus (LCANS) is a rare variant of anomalous aortic origin of a coronary artery that is not characterized by an interarterial course. Despite the absence of an interarterial course, there are rare reports of LCANS presenting with sudden death, life-threatening arrhythmia, exercise-induced myocardial ischemia, premature ventricular contractions, and syncope. We report a patient with LCANS presenting with acute myocardial infarction who recovered completely with emergent surgical unroofing of the coronary artery.